MANAJEMEN KEARSIPAN DI MAN 1 DELI SERDANG - Lia Windari Nasution (Hijri, 2020)
This research aims to describe the POAC (Planning, Organizing, Actuating, Controling) of archiving, namely: 1) Describe the process of archiving planning, 2) Describe the process of organizing archives, 3) Describe the process of implementing archives, 4) Describe the process of monitoring records at MAN 1 Deli Serdang. This research was conducted at MAN 1 Deli Serdang which is located in Medan Senembah Village, Tanjung Morawa District, Deli Serdang Regency, North Sumatra Province. The approach in this research uses a descriptive qualitative approach. The informants in this study were the Head of Madrasah, the Head of Administration and his Staff, and the Deputy Head of the School for Facilities and Infrastructure. Data collection techniques use methods, namely the observation method is carried out by the researcher observing and participating directly in the process of implementing, organizing, implementing and monitoring of archiving, interviews are conducted using a list of questions for resource persons according to the researcher's theme, and documentation is carried out by collecting data which has been available in the form of photos, reports or documents. The results of this study indicate that: archive planning includes (1) good archive creation which includes managing incoming mail, outgoing mail, archive retention schedules, and procurement of asip facilities. (2) organizing archives includes the preparation of classification patterns, recording and distribution of archives. (3) implementation of archives includes providing motivation to archive managers, maintaining communication with archive administrators. (4) supervision includes assignment direction to archive management, archive evaluation program, and supervision program after the archive is carried out